2022
DOI: 10.3390/jcm11185257
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Long-Term Prognosis of Post-Intensive Care Syndrome after Sepsis: A Single-Center Prospective Observational Study

Abstract: Post-intensive care syndrome (PICS) comprises physical, mental, and cognitive disorders following a severe illness. The impact of PICS on long-term prognosis has not been fully investigated. This study aimed to: (1) clarify the frequency and clinical characteristics of PICS in sepsis patients and (2) explore the relationship between PICS occurrence and 2-year survival. Patients with sepsis admitted to intensive care unit were enrolled. Data on patient background; clinical information since admission; physical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…Post- intensive care syndrome (PICS) has recently received considerable attention and could be a prominent example of such factors. A single-center prospective study conducted in Japan found that 70% of patients experienced PICS three months after contracting sepsis [20]. The study identified Glasgow coma scale (GCS) on day 7 as an independent, reliable marker for PICS, rather than any variables related to sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Post- intensive care syndrome (PICS) has recently received considerable attention and could be a prominent example of such factors. A single-center prospective study conducted in Japan found that 70% of patients experienced PICS three months after contracting sepsis [20]. The study identified Glasgow coma scale (GCS) on day 7 as an independent, reliable marker for PICS, rather than any variables related to sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of PICS has been reported to be 50%–70% at 6 months following ICU discharge. 12 , 65 Based on the combined data of our study and an integrated analysis of diagnostic procedure 5 , 66 in Japan, the annual number of patients with PICS following sepsis is thought to be approximately 420,000. Furthermore, PICS at 3 months was related to the significant increase in 2‐year mortality in patients with sepsis, addressing the profound impact of PICS on the long‐term mortality of patients in the ICU.…”
Section: Pics‐related Disordersmentioning
confidence: 97%
“…Furthermore, PICS at 3 months was related to the significant increase in 2‐year mortality in patients with sepsis, addressing the profound impact of PICS on the long‐term mortality of patients in the ICU. 66 …”
Section: Pics‐related Disordersmentioning
confidence: 99%
“…The “post-sepsis syndrome (PSS)” associates physical, medical, cognitive, and mental health sequalae, responsible of long-term morbidity [ 16 ]. Prior to PSS, the post-intensive care syndrome (PICS) involves physical, cognitive, and mental impairments occurring during ICU stay or after ICU/hospital discharge, impairing the long-term outcome of survivors [ 94 – 98 ]. In order to combat PSS and PICS, post discharge rehabilitation strategies are effective and associated with a reduced risk of 10-year mortality in sepsis survivors [ 99 ].…”
Section: Prehospital Emergency Care and Strategymentioning
confidence: 99%